Sλ - entropies (1987)
Those entropies H which are characterized by the property that H(P*Q) = H(P) S H(Q) for an Archimedean semigroup operation S will be expressed by additive entropies. The family with respect to the operations S λ (x,y) = x+y+ A xy will be considered. Almost all entropies known from the literature become special cases. A coding theorem is derived and conditional entropies are constructed.